The Role of Women in Advertisements - Prakash, Rashmi (Indian Journal of Marketing, 2008)
Advertising seems to be obsessed with gender and sexuality and continues to represent an arena in which gender display plays a major role. It has emerged as a world of ’commercial realism’ in which we are given ’realistic’ images of domestic life and male-female relationships which are not actually real but which provide us with a ’stimulated slice of life’. As gender representation is such a dominant feature of modern-day advertising, it is often called the social resource ’used most’ by advertisers. The changing role of women in society has created a challenging task for advertisers - how to portray women in advertisements.